In Vivo Measurement of Rotator Cuff Tendon Strain With Ultrasound Elastography: An Investigation Using a Porcine Model. (1st September 2014) - Hatta, Taku; Yamamoto, Nobuyuki; Sano, Hirotaka; Itoi, Eiji
Abstract : Objectives: To clarify the relationship between the strain ratio measured by ultrasound elastography and the mechanical properties of the tendon measured by a universal testing machine. We also attempted to determine the effect of the type and depth of soft tissue overlying the tendon on the elastographic measurement. Methods: Twelve fresh porcine shoulders were prepared. Elastographic measurement was performed on the infraspinatus tendon by manually applying repetitive compressions from an ultrasound probe with an acoustic coupler consisting of an elastomer with definite elasticity as a reference material. The strain ratio, defined as tendon/reference strain, was obtained by 4 different approaches: with the probe placed on the skin, on the subcutaneous fat after removing the skin, on the muscle after removing the subcutaneous fat, and directly on the tendon. The strain ratios measured by these approaches were compared statistically. The relationship between the depth of the tendon measured on elastography and the strain ratio was also investigated. We also attempted to clarify the relationship between the strain ratio of the tendon and its elastic property. The tendon was mounted on a testing machine, and compressive force was applied. Tendon compliance was calculated as the reciprocal of the Young modulus in the range of 5% to 10% strain, which was compared to its strain ratio. Results: The tendon/reference strain ratio significantly correlated with the tendon compliance ( r = 0.73; P < .01). The strain ratio was not affected by differences in the measuring approaches ( P = .4) or by the depth to the tendon level ( P = .8). Conclusions: Our results indicated that the strain ratio of the rotator cuff tendon could be measured with minimal influence by overlying soft tissues if its depth from the skin was less than 22 mm. We believe that ultrasound elastography would be a useful tool for assessment of tendon elasticity in clinical practice.